Cholesteric films exhibiting expanded or split reflection bands prepared by atmospheric photopolymerisation of diacrylic nematic monomer doped with a photoresponsive chiral dopant. Issue 15 (9th March 2015) - Harada, Y.; Sakajiri, K.; Kuwahara, H.; Kang, S.; Watanabe, J.; Tokita, M.
Abstract : Cholesteric films exhibiting expanded or split reflection bands prepared by atmospheric photopolymerization of nematic diacrylate doped with a photoresponsive chiral dopant. Abstract : Cholesteric liquid crystal (CLC) films with gradient pitches are prepared by atmospheric UV irradiation of mixtures of a diacrylic nematic monomer (M), a macrocyclised chiral cinnamate dimer (CD), and a photoinitiator (PI). UV light induces the intramolecular photodimerisation of the two cinnamate moieties in the CD to decrease the helical twisting power. The CLC of 90/10 (w/w) mixture of M/CD exhibits an optical pitch of 482 nm, which increases homogeneously to 815 nm upon atmospheric UV irradiation of the film. When the CLC doped with 1.5 wt% PI is formed into a planar-aligned film and irradiated with UV light in the atmosphere, the CLC film exhibits pitches that increases toward the air-interface side so as to result in a wide reflection band ranging from 420 to 890 nm; in addition, the film assumes a silver appearance. When the PI concentration and UV intensity are increased, the spectra of the CLC films exhibit two reflection bands and films assume a magenta colour. Such pitch distributions result from the confliction between untwisting and polymerisation of the CLC, both of which are induced by the UV light, although the polymerisation rate is decreased by the diffusion of atmospheric oxygen into the film.